Instrumen Bank Wakaf Mikro: Alternatif Pemberdayaan Ekonomi Pesantren - Alan Suud Maadi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2018)
This articel provides a model of clarification or a strategic instrument for Micro Waqaf Bank in an effort to empower the pesantren economics and society living around the boarding school. Micro waqaf Bank Endowments Banks on the definition of the concept of waqf which is a unique and growing financial instrument in Islamic countries. But in Indonesia has not been optimally empowered because during this time the property used goods that are not moving and not productive. This article describes the model theory or instrument of Wakaf Micro Bank which is ideal and suitable to be applied in pesantren in disaster management by empowering economy through various sharia compliance investments. The method used is a library reseach of literature books, articles, journals and internet. Results from Micro Endowments Bank for the economic development of pesantren and arround communities.